Penerapan Karakter Tanggung Jawab Dalam Proses Pembelajaran Di SD Negeri Limpok Aceh Besar - Silvira Nurul Sabila; soedirman Soedirman; Sulaiman Sulaiman (Universitas Syiah Kuala, 2022)
This research was conducted to see how teachers apply the personality of responsibility for learning methods at SD Negeri Limpok Aceh Besar. The approach that is used as a reference in this research is a qualitative approach. The data of this study came from the results of interviews with classroom teachers, while the data sources were high-class teachers at SD Negeri Limpok. The data was combined using observation and question and answer methods. The observation method used is to see how the teacher applies the personality of responsibility to the learning method. While the question and answer method was applied to interviewing high grade teachers at SD Negeri Limpok. This study shows how teachers have implemented several responsible personalities for learning methods including by always fostering students before and after the learning process, showing an attitude of responsibility to students, and providing reinforcement to students that the implementation of a responsible personality will make the assessment phase a difficult one. effective, able to make changes to student learning outcomes, grade IV teachers have implemented the personality of responsibility for learning methods well while teachers of grades V and VI have not implemented the personality of responsibility for learning methods well because they have not implemented all the indicators that have been determined. The teacher has applied the responsible personality to the learning process effectively.